2014
DOI: 10.1002/adma.201402404
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Electronic and Structural Transitions in VO2 Observed Using X‐ray Absorption Spectromicroscopy

Abstract: The popular dual electronic and structural transitions in VO2 are explored using X‐ray absorption spectromicroscopy with high spatial and spectral resolutions. It is found that during both heating and cooling, the electronic transition always precedes the structural Peierls transition. Between the two transitions, there are intermediate states that are spectrally isolated here.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 46 publications
(121 reference statements)
2
65
0
Order By: Relevance
“…O1s to O2p states, in which two distinct features of the t 2g and e g peaks reflected the unoccupied states [26,27]. The intensity ratio of t 2g /e g decreased substantially with…”
Section: (D) Presented the Transitions Frommentioning
confidence: 98%
“…O1s to O2p states, in which two distinct features of the t 2g and e g peaks reflected the unoccupied states [26,27]. The intensity ratio of t 2g /e g decreased substantially with…”
Section: (D) Presented the Transitions Frommentioning
confidence: 98%
“…The vanadium K-edge XANES high-resolution spectroscopy has been shown to have the sensitivity to probe the local structure changes associated with the MIT transition [52]. Moreover, a local probe such as XANES may investigate simultaneously both the MIT and the SPT, monitoring the local behaviour of VO 2 films at the O K-edge [53].…”
Section: Mesoscience and The Phase Separation Scenario In Correlated mentioning
confidence: 99%
“…Recent results using X-ray absorption spectromicroscopy [53] showed that it is possible to induce an electronic transition without inducing a structural transition in thin film of VO 2 during a heating-cooling cycle. This experiment is an additional demonstration of the relevance of used techniques with high spectral, time and spatial resolution, to accurately study inhomogeneous media such as phase separated materials and with complex multi-dimensional phase diagrams.…”
Section: Mesoscience and The Phase Separation Scenario In Correlated mentioning
confidence: 99%
“…3-6 Some of the important scientific issues recently addressed include the nature and sequence of the transitions, 7,8 effect of surface charges, 9,10 role of joule heating during resistance switching, 11,12 phase diagram of the transitions, 13 etc. There have been debates and contradicting results on several of these issues.…”
mentioning
confidence: 99%
“…This is very consistent with our previous experimental result using a more direct and detailed mapping of the two transitions in the same film of VO2 used here. 8 To better compare the transitions observed in the infrared, visible and x-ray transmission, and the resistance, we used the 2-dimensional Bruggeman effective medium approximation (EMA) for percolative media to calculate the macroscopic resistance (black curve in Figure 3a) by parametrically varying the volume fraction of the component phases with different resistivities (using terminal resistance values from Figure 1b for heating and cooling braches separately). [29][30][31] We then use the normalized transmission of Figure 1b as indicative of the phase fractions (Φ) measured by infrared and visible lights and map them to the resistance of the film at the corresponding temperatures ( Figure 3a).…”
mentioning
confidence: 99%